2014
DOI: 10.1093/jnci/dju083
|View full text |Cite
|
Sign up to set email alerts
|

Overactivated Neddylation Pathway as a Therapeutic Target in Lung Cancer

Abstract: Our study highlights the overactivated neddylation pathway in lung cancer development and as a promising therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
186
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(205 citation statements)
references
References 44 publications
15
186
1
Order By: Relevance
“…This significant apoptotic response was attributed to the induction of c-FLIP degradation, which the authors showed to be independent of NEDD8 inhibition (67). Furthermore, it is now abundantly clear that hundereds of cellular proteins are regulated through neddylation, and consistently, pevonedistat inhibits several signal transduction pathways, including the NFkB, AKT, and the mTOR signaling pathways, in addition to cullin-signaling (28,29,(63)(64)(65)(66). Thus, pevonedistat may exhibit differential toxicities in HNSCC cells and tumors depending on the genetic backgrounds of the cells or tumors as well as on the concentrations employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This significant apoptotic response was attributed to the induction of c-FLIP degradation, which the authors showed to be independent of NEDD8 inhibition (67). Furthermore, it is now abundantly clear that hundereds of cellular proteins are regulated through neddylation, and consistently, pevonedistat inhibits several signal transduction pathways, including the NFkB, AKT, and the mTOR signaling pathways, in addition to cullin-signaling (28,29,(63)(64)(65)(66). Thus, pevonedistat may exhibit differential toxicities in HNSCC cells and tumors depending on the genetic backgrounds of the cells or tumors as well as on the concentrations employed.…”
Section: Discussionmentioning
confidence: 99%
“…Pevonedistat inhibits all cullin-based E3 ligases and additionally exhibits cullin-independent activity (28,29,(63)(64)(65)(66)(67). However, the results described above suggest that the radiosensitizing activity of pevonedistat is due to its ability to induce rereplication, which can be enhanced by IR.…”
Section: Induction Of Rereplication Via Cdt2 Depletion or Cdt1 Activamentioning
confidence: 98%
“…Neddylation is a novel type of posttranslational modification that adds the ubiquitin-like molecule NEDD8 to substrate proteins and thus regulates their function (1)(2)(3). This process is catalyzed by a cascade comprising the NEDD8-activating enzyme E1 (NAE, NAE1 and UBA3 heterodimer), NEDD8-conjugating enzyme E2, and substrate-specific NEDD8-E3 ligases (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Neddylation is a novel type of posttranslational modification that adds the ubiquitin-like molecule NEDD8 to substrate proteins and thus regulates their function (1)(2)(3). This process is catalyzed by a cascade comprising the NEDD8-activating enzyme E1 (NAE, NAE1 and UBA3 heterodimer), NEDD8-conjugating enzyme E2, and substrate-specific NEDD8-E3 ligases (1)(2)(3). The best known substrates of neddylation are cullin family proteins, the essential subunits of multiunit Cullin-RING E3 ubiquitin ligases (CRL) whose dysfunction leads to tumorigenesis and tumor progression (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation